Human Mandible Prenatal Morphogenesis - Kabak, Sergey Lvovich; Zhuravleva, Natalia Victorovna; Melnichenko, Yuliya Michailovna (Journal of Morphological Sciences, 2019)
Introduction This study was performed with the aim of detecting the interaction between cartilaginous and bone tissues in the process of mandible morphogenesis in human embryos.Material and Methods Whole-mount skeletal preparations, stained with Alcian blue and Alizarin red, as well as serial histological sections impregnated with silver and stained with hematoxylin and eosin were studied. A total of 48 human embryos/fetuses from 5 to 29 weeks of age were used.Results In the mandible anlage, in addition to the woven bone, cartilaginous and chondroid tissues are present. Cartilaginous tissue islets are localized at the tip of the condylar and coronoid processes and also in the region of the mandibular symphysis. The chondroid tissue is incorporated into the bone in the region of the mandibular symphysis, along the edge of the coronoid process, and also in the alveolar part of the mandible.Conclusion Meckel’s cartilage participates in the formation of the mandibular body, and its remains persist in the area of the mandibular symphysis until the second half of the prenatal development.
Keywords: mandible; human development; Meckel’s cartilage; chondroid tissue; condylar cartilage